L’ethnologie, un métier du patrimoine ? Réflexions autour de la question du patrimoine culturel immatériel - Christian Hottin (In Situ)
This article does not set out to retrace the place of ethnology and ethnologists in the recent history of France’s heritage administration at the Ministry of Culture. Rather, it will take a closer look at how these ethnologists reacted to the drawing up, in the middle of the 2000s, of the UNESCO convention on intangible cultural heritage (‘patrimoine culturel immatériel’ in French, PCI). This convention was ratified by the French government in 2006 and led to a modification in the work habits of the service in charge of ethnology within the Ministry. Traditionally, this service was used to working with professional ethnologists in cultural spheres or in university contexts. The reactions to the UNESCO convention cover a complex range of attitudes, presented here, ranging from enthusiastic adhesion to the principles and operational features of the convention to their radical rejection and covering, in between, various forms of critical involvement. Without making any pretence at a complete survey, we will try to analyse these attitudes in the perspective of the relations between ethnologists and the heritage over the past 35 years during which the French ministry of Culture has had a policy for ethnology.